Crosstalk Between ATP-P2X7 and Adenosine A2A Receptors Controlling Neuroinflammation in Rats Subject to Repeated Restraint Stress - Dias, Liliana (2021)
Depressive conditions precipitated by repeated stress are a major socio-economical burden in Western countries. Previous studies showed that ATP-P2X7 receptors (P2X7R) and adenosine A2A receptors (A2AR) antagonists attenuate behavioral modifications upon exposure to repeated stress. Since it is unknown if these two purinergic modulation systems work independently, we now investigated a putative interplay between P2X7R and A2AR. Adult rats exposed to restraint stress for 14 days displayed an anxious (thigmotaxis, elevated plus maze), depressive (anhedonia, increased immobility), and amnesic (modified Y maze, object displacement) profile, together with increased expression of Iba-1 (a marker of microglia "activation") and interleukin-1β (IL1β) and tumor necrosis factor α (TNFα; proinflammatory cytokines) and an up-regulation of P2X7R (mRNA) and A2AR (receptor binding) in the hippocampus and prefrontal cortex. All these features were attenuated by the P2X7R-preferring antagonist brilliant blue G (BBG, 45 mg/kg, i.p.) or by caffeine (0.3 g/L, p.o.), which affords neuroprotection through A2AR blockade. Notably, BBG attenuated A2AR upregulation and caffeine attenuated P2X7R upregulation. In microglial N9 cells, the P2X7R agonist BzATP (100 μM) or the A2AR agonist CGS26180 (100 nM) increased calcium levels, which was abrogated by the P2X7R antagonist JNJ47965567 (1 μM) and by the A2AR antagonist SCH58261 (50 nM), respectively; notably JNJ47965567 prevented the effect of CGS21680 and the effect of BzATP was attenuated by SCH58261 and increased by CGS21680. These results provide the first demonstration of a functional interaction between P2X7R and A2AR controlling microglia reactivity likely involved in behavioral adaptive responses to stress and are illustrative of a cooperation between the two arms of the purinergic system in the control of brain function.